PENERAPAN PROGRAM SEKOLAH+NGAJI MELALUI TILAWATI DALAM PEMBIASAAN MENCINTAI AL-QUR’AN - Nurul Jannah (Educare : Jurnal Ilmu Pendidikan, 2022)
This study aims to describe the implementation or application of the 'Sekolah+Ngaji' Program as a habit of loving the Qur'an from an early age in RA Khodijah II Sebaung, Gending District. The 'Sak Ngajne School' program is taken from the Javanese language which means School While Reciting the Qur'an. This habituation program is packaged in Al-Qur'an learning activities using the Tilawati method. This research uses a qualitative descriptive approach with the type of case study. From this study, it was found that the 'Sekolah+Ngaji' program can condition the tendency of children to be active and have difficulty concentrating so that the quality and quantity targets can be achieved well in learning the Qur'an. Through the 'Sak Ngajine School' program, it can have a very good impact on students, namely instilling the habit of learning the Qur'an to students so that they are able to foster a sense of love for the Qur'an from an early age in RA Khodijah II Sebaung, Gending District, Probolinggo Regency. The implication is that learning the Qur'an to early childhood requires creativity, patience, and patience from teachers in teaching